Dynamics of pathological changes of myocardial structures of rats under administration of doxorubicin - А. G. Rodinskij; Ju. V. Kozlova; L. V. Guz' (Patologìâ)
Due to the high cardiotoxicity of doxorubicin it is used to study pathogenesis of heart failure.